PLK1 and PARP positively correlate in Middle Eastern breast cancer and their combined inhibition overcomes PARP inhibitor resistance in triple negative breast cancer - Siraj, Abdul K.; Poyil, Pratheesh Kumar; Padmaja, Divya; Parvathareddy, Sandeep Kumar; Alobaisi, Khadija; Thangavel, Saravanan; Diaz, Roxanne; Begum, Rafia; Almalik, Osama; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Oncology, 2024)
Background Despite advancements in treatment approaches, patients diagnosed with aggressive breast cancer (BC) subtypes typically face an unfavorable prognosis. Globally, these cancers continue to pose a significant threat to women's health, leading to substantial morbidity and mortality. Consequently, there has been a significant struggle to identify viable molecular targets for therapeutic intervention in these patients. Polo-like Kinase-1 (PLK1) represents one of these molecular targets currently undergoing rigorous scrutiny for the treatment of such tumors. Yet, its role in the pathogenesis of BC in Middle Eastern ethnicity remains unexplored. Methods We investigated the expression of PLK1 protein in a cohort of more than 1500 Middle Eastern ethnicity BC cases by immunohistochemistry. Association with clinicopathological parameters and prognosis were performed. In vitro studies were conducted using the PLK1 inhibitor volasertib and the PARP inhibitor olaparib, either alone or in combination, in PTC cell lines. Results Overexpression of PLK1 was detected in 27.4% of all BC cases, and this was notably correlated with aggressive clinicopathological markers. PLK1 was enriched in the triple-negative breast cancer (TNBC) subtype and exhibited poor overall survival (p = 0.0347). Notably, there was a positive correlation between PLK1 and PARP overexpression, with co-expression of PLK1 and PARP observed in 15.7% of cases and was associated with significantly poorer overall survival (OS) compared to the overexpression of either protein alone (p = 0.0050). In vitro, we studied the effect of PLK1 and PARP inhibitors either single or combined treatments in two BRCA mutated, and one BRCA proficient TNBC cell lines. We showed that combined inhibition significantly reduced cell survival and persuaded apoptosis in TNBC cell lines. Moreover, our findings indicate that inhibition of PLK1 can reinstate sensitivity in PARP inhibitor (PARPi) resistant TNBC cell lines. Conclusion Our results shed light on the role of PLK1 in the pathogenesis and prognosis of Middle Eastern BC and support the potential clinical development of combined inhibition of PLK1 and PARP, a strategy that could potentially broaden the use of PLK1 and PARP inhibitors beyond BC cases lacking BRCA.